Granulomatous inflammation by candida presenting as a hard subcutaneous nodule: A rare case report with review of literature - Swati Garg; Abhijit Das; Natasha Gulati; Madhu Sinha (Wolters Kluwer Medknow Publications, 2020)
Fungal infections are very important infectious causes of granulomatous inflammation. Isolated subcutaneous fungal infections are uncommon and only seen in immunosuppressed patients or in those with other comorbidities. Such cases are usually mistaken as noninfectious benign lesions and fine-needle aspiration cytology (FNAC) can be used for an adequate diagnosis.